(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
The case study describes a high-risk substance user adult patient with Nubain, smoking, and alcohol abuse. This research study tries to find out the effect of substance abuse on the patient’s health and social functioning. Initially, the patient started with marijuana for fun with friends, which further led to Nubain injections, alcohol intake, and smoking. Due to prolonged consumption, the patient’s body eventually developed an intolerance to these substances, resulting in severe health complications. The patient was admitted to a nearby hospital in emergency with sudden severe abdominal pain. The patient was diagnosed with CBC, ultrasound, and x-ray to identify his condition. The complications were so serious that the patient needed the attention of a specialized doctor, including very low hemoglobin levels and melena. Despite all these admissions and other medical interventions, there was no improvement in the patient’s condition. The patient ultimately died due to substance use. This study identifies early intervention and comprehensive care as important in improving health and social outcomes. It points to the dangerous and lethal effects of substance abuse, hence the importance of prevention and timely medical interventions.